Quality of Life Cervical Cancer Patients Stage IB-IIB After Neoadjuvant Chemotherapy Followed by Surgery Versus Surgery Alone - Arista, Nurkamilawati; Utama Pelupessy, Nugraha; Butje Leonardy, Rudy; Hamid, Firdaus; Arifuddin, Sharvianty; Susiawaty (International Journal of Psychosocial Rehabilitation, 2020)
Cervical cancer is the leading cause of death after breast cancer. The research aimed to determine the effect of giving adjuvant chemotherapy on quality of life in cervical cancer patients stage IB-IIB. Forty-three cervical cancer patients stage IB-IIB who were established based on history taking, physical examination, biopsy, radiology, laboratory, and clinical staging were included in this study. Platinum-based chemotherapy was performed in three to six series, followed by surgery in group one (24 respondents) and surgery alone in group two (19 respondents). The EORTC QLQ 30 and EORTC CX-24 questionnaires were administered after twenty-one days after surgery. An analysis of the results of the post-chemotherapy laboratory results was also carried out, the results of the operating outcomes, and a comparison of estimated treatment costs. Analytical test results showed levels of leukocytes (p = 0.002) and platelets (p = 0.001), which were both lower in the NACT+surgery group. At estimated maintenance costs, p <0.001 was higher in the NACT + surgery group. There are ten respondents with a complete response and nine respondents with a partial response postchemotherapy. Positive LVSI was obtained at 25% vs. 57.89% and lymph node metastasis at 25% vs. 31.58%. From the results of the EORTC QLQ 30 and EORTC CX-24 questionnaires, there were significant values of fatigue symptoms (p = 0.017), appetite loss (p = 0.004), sexual function (p = 0.019), sexual activity (p = 0.033), and enjoyment sexual (p = 0.048) where everything was worse in the NACT + surgery group. Whereas vaginal symptoms were higher in the surgery group alone (p = 0.049). The results of evaluating QoL were lower after NACT administration, and sexuality was the most affected in the NACT group. But NACT administration improves operability and histopathological results